Decarboxylation mechanisms of C4 photosynthesis in Saccharum spp.: Increased PEPCK activity under water-limiting conditions - Cacefo, Viviane; Ribas, Alessandra Ferreira; Zilliani, Rafael Rebes; Neris, Daniel Moreira; Domingues, Douglas Silva [UNESP]; Moro, Adriana Lima; Vieira, Luiz Gonzaga Esteves (Springer Nature, 2019)
Background: C4 plants have been classified into three subtypes based on the enzymes used to decarboxylate C4 acids in the bundle sheath cells (NADP-ME, NAD-ME and PEPCK pathways). Evidences indicate that, depending on environmental factors, C4 plants may exhibit a certain degree of flexibility in the use of the decarboxylation mechanisms. In this context, the objective was to extend the knowledge on the degree of flexibility between the pathways of decarboxylation in sugarcane, a NADP-ME species, at different levels of water deficit. Results: An experiment was carried out with two cultivars - RB92579 (tolerant to water deficit) and SP80-3280 (susceptible to water deficit) subjected to moderate level (- 1.5 to - 1.8 MPa), severe level (below - 2.0 MPa) and recovery (48 h after rehydration) and changes in the activities of the enzymes involved in the three C4 mechanisms and in gene expression were investigated. Our results showed that sugarcane uses the PEPCK pathway as a decarboxylation mechanism in addition to the NADP-ME, which was more evident under water deficit conditions for both cultivars. Conclusions: The results obtained here, show that sugarcane increases the use of the PEPCK pathway as a decarboxylation mechanism, in addition to the NADP-ME pathway, under conditions of water deficit, particularly in the tolerant cultivar.
Keywords: Saccharum spp. drought stress. C4 photosynthesis. Decarboxylation mechanisms. Gene regulation